A powerful combination of liquid chromatography-triple quadrupole mass spectrometry and quadruple isotope dilution strategy for the determination of fenuron at trace levels in river water, stream water and fruit juice samples - Bodur, Sueleyman; Erarpat, Sezin; Gunkara, Omer Tahir; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
An accurate, sensitive, and rapid analysis methodology for the determination of fenuron at ultratrace levels in river water, stream water and fruit juice samples was developed based on quadruple isotope dilution (ID4) and liquid chromatography-triple quadrupole mass spectrometry (LC-MS/MS) system. Fenuron-d6 as isotopically labelled material (ILM) was synthesized in our laboratory to apply the ID4 method. Optimization studies were performed to find experimental conditions for the separation and detection of fenuron at trace levels. Analytical performance parameters such as limit of detection (LOD), limit of quantitation (LOQ) and linear range were determined by external calibration strategy. LOD and LOQ values for the analyte were found at ppt levels and a wide linear range was obtained in the range of 0.11 - 492.4 & mu;g/kg. Recovery studies were also carried out for water and fruit juice samples to test applicability and accuracy of the developed LC-MS/MS system. ID4 strategy was applied to the selected samples to increase accuracy of the developed method and tolerate high matrix effects for fruit juice samples. According to high percent recoveries and low relative standard deviation values, the developed LC-ID4-MS/MS system was proven as an accurate, precise and sensitive analytical method for the quantification of fenuron at trace levels.
Keywords: Fenuron; Quadruple isotope dilution; Liquid chromatography-triple quadrupole mass; spectrometry; PESTICIDE-RESIDUES; HERBICIDES; PHENYLUREA; LIMITS; Chemistry; Food Science & Technology